Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $p(x)$ is a polynomial of degree 4 such that $p(2)=p(-2)=p(-3)=-1$ and $p(1)=p(-1)=1$, then find $p(0)$.

share|cite|improve this question
Since the polynomial has degree 4 it is in the form $p(x) = ax^4 + bx^3 + cx^2 + dx + e$. Now how would you figure out the coefficients? – Null Sep 2 '14 at 18:16
Have you had matrices in a class? – Paul Sundheim Sep 2 '14 at 18:18
Hint: Lagrange interpolation. – Robert Israel Sep 2 '14 at 18:44

Using a difference table, with $p(0)=c$, gives

$-1\hspace{.5 in}-1\hspace{.5 in}1\hspace{.5 in}c\hspace{.6 in}1\hspace{.5 in}-1$

$\hspace{.4 in}0\hspace{.64 in}2\hspace{.43 in}c-1\hspace{.35 in}1-c\hspace{.4 in}-2$

$\hspace{.7 in}2\hspace{.47 in}c-3\hspace{.2 in}-2c+2\hspace{.2 in}-3+c$

$\hspace{.9 in}c-5\hspace{.3 in}-3c+5\hspace{.3 in}3c-5$

$\hspace{1.1 in}-4c+10\hspace{.3 in}6c-10$

$\hspace{1.5 in}10c-20$

Then $10c-20=0\implies c=2$.

share|cite|improve this answer
Very well observed! – Yves Daoust Sep 2 '14 at 20:11
@Yves Daoust Thanks - I just wanted to check that this method gave the same answer as Lagrangian interpolation. – user84413 Sep 2 '14 at 20:13

Let $\displaystyle p(x)=(Ax+B)(x-2)(x+2)(x+3)-1,$ where $A,B$ are arbitrary finite constants


Set $x=1,-1$ one by one to find $B$

share|cite|improve this answer
You have $p(2)=1$ not -1 as the OP has stated. – Paul Sundheim Sep 2 '14 at 18:21
@PaulSundheim, Hope you understood the typo. Thanks for your observation – lab bhattacharjee Sep 2 '14 at 18:23
Would have been useful to explain that you first factorize $p(x)+1$, knowing three roots. – Yves Daoust Sep 2 '14 at 19:43

This is a case of Lagrangian interpolation.

$$P(x)=\sum_i\left(y_i\prod_{j\ne i}\frac{x-x_j}{x_i-x_j}\right).$$

It is most efficiently computed using Neville's scheme.

Using the abscissas in the order $-3, -2, -1, 1, 2$, the triangle of interpolated values is: $$-1,\ -1,\ 1,\ 1,\ -1$$ $$-1,\ 3,\ 1,\ 3$$ $$5,\ \frac53,\ \frac53$$ $$\frac52,\ \frac53$$ $$\color{blue}2$$

enter image description here

share|cite|improve this answer

Put $q(x)=p(x)-p(-x)$. Then $p$ is an odd polynomial, of degree $\leq 3$. Hence $p(x)-p(-x)=xq(x^2)$ with degree of $q\leq 1$, say $q(y)=ay+b$. We have $q(1)=q(4)=0$, hence as degree of $q$ $\leq 1$, $q=0$ and $p(x)=p(-x)$. We get $p(-3)=p(3)=-1$, and so $p(x)=c(x^2-4)(x^2-9)-1$ for a constant $c$, and we finish easily.

share|cite|improve this answer

For later simplification, consider $p_1(x)=p(x)+1$, that has three known roots. We see that $p_1(x)$ is an even function, so that $p_1(x)=ax^4+bx^2+c=a(x^2)^2+bx^2+c=q(x^2)$.

$q(x^2)$ is of the second degree in $x^2$, and much easier to interpolate. We have $q(1)=2$, $q(4)=q(9)=0$, hence by Lagrange $q(0)=2\frac{(0-4)(0-9)}{(1-4)(1-9)}=3=p_1(0)$, and $p(0)=\color{blue}2$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.